1997
DOI: 10.1063/1.473220
|View full text |Cite
|
Sign up to set email alerts
|

The transition from single phonon to multiphonon energy transfer in atom–surface collisions

Abstract: A helium atom scattering study of the structure and phonon dynamics of the ice surface Energy and momentum transfer of He atoms scattered from a lithium fluoride crystal surfaceThe angular distributions and time-of-flight spectra of nearly monoenergetic He atoms with incident energies of 82 meV and 112 meV have been measured after scattering from a clean Cu͑001͒ surface over a large range of crystal temperatures from 100 K to 1000 K. With increasing temperatures the sharp diffraction and phonon peaks of the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 80 publications
1
12
0
Order By: Relevance
“…The atomic smooth-surface model has been used successfully to explain a large number of experimental results for both measured angular distributions and energy resolved intensities for rare gases such as He, Ne, Ar, and Xe scattering from a variety of insulator, metal, and liquid metal surfaces. 26,34,36,41,42 The good agreement obtained for the angular distributions in this work shows that a similar model, extended to include rotational motion, appears to explain the multiple phonon energy exchange in classical moleculesurface scattering.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The atomic smooth-surface model has been used successfully to explain a large number of experimental results for both measured angular distributions and energy resolved intensities for rare gases such as He, Ne, Ar, and Xe scattering from a variety of insulator, metal, and liquid metal surfaces. 26,34,36,41,42 The good agreement obtained for the angular distributions in this work shows that a similar model, extended to include rotational motion, appears to explain the multiple phonon energy exchange in classical moleculesurface scattering.…”
Section: Discussionsupporting
confidence: 54%
“…The Rayleigh velocity for LiF͑001͒ depends on crystal azimuth, but is approximately 4000 m/s. 40 In previous multiphonon studies of atomsurface scattering carried out for both insulator and metal substrates, v R has been fit to values less than the Rayleigh velocity, 41,42 but has also sometimes appeared to be dependent on the incident energy. 26,34 In this case the values of v R which allowed for the good fits with the data increased with energy, with v R ϭ130 m/s for the lowest energy E i T ϭ110 meV, v R ϭ520 m/s for E i T ϭ275 meV, and v R ϭ1050 m/s for E i T ϭ618 meV.…”
Section: A Angular Distributionsmentioning
confidence: 99%
“…When the range of the potential and the corrugation amplitude are limited i.e. much smaller than the lattice parameter, this surface is close to the corrugation functionZ(y), and the HCW is known to be qualitatively correct [35][36][37]. However, the accuracy of the HCW model can be limited and corrugation amplitudes with departures up to 30% from exact theoretical treatments have been reported [24].…”
Section: Simplified Description Within the Hard Corrugated Wall Mmentioning
confidence: 94%
“…The effective surface phonon velocity y R was chosen to be 130 m͞s for the lowest energy E T i 110 meV, 520 m͞s for E T i 275 meV, and 1050 m͞s for E T i 618 meV. The value of y R is expected to be significantly smaller than the Rayleigh wave velocity [10], which is about 4000 m͞s for LiF [2,9], and previous treatments of atomic scattering have indicated that y R is energy dependent with values increasing with higher incident energy [8,13]. The value of v R is chosen to be 2 3 10 10 s 21 and the mass M C of the surface is taken to be 51.9 amu which is 2 times the mass of LiF.…”
mentioning
confidence: 99%